Transmettre l’histoire de l’Afrique - Bertrand Hirsch (Afriques)
Through critical readings of several works on Africa and its history, the aim of this note is to understand that which, in the transmission of the history of African societies, does not work, or works less well than in other regions and civilizations. Why do we tolerate a general amateurism, or “approximate” approach? Chronological or geographic confusion and errors, as well as risky short cuts, are perpetuated or re-emerge in new forms for a rather simple reason: they are not detected, as if they had no significance. Consequently, there is no common knowledge on the history of Africa, no more in learned circles than among the general public or journalists.